2011
DOI: 10.1038/oby.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

The Individual and Combined Effects of Glycemic Index and Protein on Glycemic Response, Hunger, and Energy Intake

Abstract: Although high protein and low glycemic index (GI) foods are thought to promote satiety, little is known about the effects of GI, protein, and their interaction on hunger and energy intake several hours following a mixed meal. This study investigated the long term effects of GI, protein, and their combined effects on glucose, insulin, hunger, and energy intake in healthy, sedentary, overweight, and obese adults (BMI of 30.9 ± 3.7 kg/m 2 ). Sixteen individuals participated separately in four testing sessions aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
2
13
0
2
Order By: Relevance
“…[17][18][19][20][21][22] However, glucose and insulin responses were not assessed at the subsequent meal in any of these studies. Thus, the current study was the first to examine whether this response would extend into and contribute to the 'second meal phenomenon'.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[17][18][19][20][21][22] However, glucose and insulin responses were not assessed at the subsequent meal in any of these studies. Thus, the current study was the first to examine whether this response would extend into and contribute to the 'second meal phenomenon'.…”
Section: Discussionmentioning
confidence: 96%
“…Twenty-five (25) H-BS and thirty-one (31) H-BC met the screening criteria, were available for the 8-h testing days, and began the study. Twenty (20) H-BS and fifteen (15) H-BC completed all study procedures. Both groups included overweight, late adolescent girls that showed normal fasting glucose and insulin concentrations ( Table 1).…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the difference in carbohydrate content of those breakfasts may explain the glucose results as opposed to the combined effect of protein and fiber. In contrast, one previous study [58] systematically assessed the individual and combined effects of low vs. high glycemic index (GI) and protein breakfast treatments on postprandial insulin and glucose responses. Makris et al [58] found that combining higher amounts of protein and low GI simultaneously did not have an effect on postprandial insulin and glucose responses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one previous study [58] systematically assessed the individual and combined effects of low vs. high glycemic index (GI) and protein breakfast treatments on postprandial insulin and glucose responses. Makris et al [58] found that combining higher amounts of protein and low GI simultaneously did not have an effect on postprandial insulin and glucose responses. However, intake of higher amounts of the low GI breakfast meal attenuated postprandial insulin and glucose responses.…”
Section: Discussionmentioning
confidence: 99%